Efficacy of eye drops containing crosslinked hyaluronic acid and CoQ10 in restoring ocular health exposed to chlorinated water. Issue 3 (May 2020) - Tredici, Costanza; Fasciani, Romina; Villano, Antonio; Gambini, Gloria; Caporossi, Aldo
Purpose: A prospective, open-label study in 20 professional swimmers evaluated the efficacy and safety of an ophthalmic solution containing crosslinked hyaluronic acid, coenzyme Q10, and vitamin E TPGS in releasing eye irritation and restoring ocular surface damages after prolonged exposure to chlorinated water. Methods: Individually, one eye was instilled with the ophthalmic solution and the other used as a comparator. Eye drops were self-administered three times a day for 2 months. Tear film breakup time (primary endpoint), Schirmer I test, beating of eyelashes/min, tear osmolarity, corneal and conjunctival staining with fluorescein, Ocular Surface Disease Index questionnaire, subject satisfaction, visual acuity (secondary endpoints), and Efron Grading Scale were evaluated at screening/baseline (V1), week 1 (V2), week 2 (V3), week 4 (V4), and week 8 (V5). Results: After 2 months, breakup time test significantly improved in the treated eyes (+1.67 s) compared to control (−3.00 s) ( p  = 0.0002). Corneal and conjunctival surfaces of treated eyes recovered significantly compared to control eyes when assessed by fluorescein staining ( p  < 0.0001), Ocular Surface Disease Index ( p  < 0.05), and visual analog scale ( p  = 0.0348) scores. Improvements were also observed with Schirmer I test, beating of eyelashes, and tear osmolarity, despite without statistical significance. Efron Grading Scale was consistent with the other tests. The ocular tolerability was excellent. Conclusion: The adequate combination of crosslinked hyaluronic acid, coenzyme Q10, and vitamin E TPGS, contained in the ophthalmic solution VisuXL ®, has been shown to protect ocular surface from potential damages originating from prolonged exposure to chlorinated water. VisuXL may represent a compelling treatment in other situations beyond dry eye syndrome.